Bcl-xL is an oncogenic driver in colorectal cancer - Scherr, Anna-Lena; Gdynia, Georg; Haffa, Mariam; Radhakrishnan, Praveen; Heller, Anette; Keim, Sophia; Kautz, Nicole; Jassowicz, Adam; Elßner, Christin; Jäger, Dirk; Schneider, Martin; Köhler, Bruno Christian (Cell death & disease, 2016)
Colorectal cancer (CRC) is the second most common malignant neoplasia in women and men worldwide. The B-cell lymphoma 2 (Bcl-2) protein family is mainly known for its pivotal role in the regulation of the mitochondrial death pathway. Anti-apoptotic Bcl-2 proteins may provide survival benefits and induce therapy resistance in cancer cells. Among anti-apoptotic Bcl-2 proteins, we found solely Bcl-xL strongly upregulated in human CRC specimens. In order to study protein function in the context of tumor initiation and progression in vivo, we generated a mouse model lacking Bcl-xL in intestinal epithelial cells (Bcl-xLIEC-KO). If challenged in an inflammation-driven tumor model, Bcl-xLIEC-KO mice showed a significantly reduced tumor burden with lower tumor numbers per animal and decreased tumor sizes. Analysis of cell death events by immunohistochemistry and immunoblotting revealed a striking increase of apoptosis in Bcl-xL-negative tumors. qRT-PCR and immunohistochemistry excluded changes in proliferative capacity and immune cell infiltration as reasons for the reduced tumor load and thereby identify apoptosis as key mechanism. Human CRC tissue was cultured ex vivo and treated with the small molecule compound ABT-737, which inhibits Bcl-xL and Bcl-2. Under ABT-737 treatment, the amount of apoptotic tumor cells significantly increased compared with controls, whereas proliferation levels remained unaltered. In summary, our findings identify Bcl-xL as a driver in colorectal tumorigenesis and cancer progression, making it a valuable target for clinical application.